Effects of gibberellic acid (GA3) and activated coal on in vitro culture of Citrus limonia Osbeck x Poncirus trifoliata L. Raf. embryos - Ribeiro, Valtemir Gonçalves; Sanábio, Deny; Souza, Cleber Nascimento de; Lopes, Paulo Sergio Nascimento; Bocardo, Marcelo Ramazotti; Pasqual, Moacir (Pesquisa Agropecuaria Brasileira, 2000)
This work utilized fruits of a single plant obtained from the cross between Citrus limonia Osb. c Poncirus trifoliata L. Raf. Seeds were removed and after excision, all the embryos, regardless their development stages, were inoculated in MS medium added with GA3 (0.0, 0.01, 0.1 and 1.0 mg/L) and activated coal (0.0, 0.5, 1.0 and 2.0 g/L) in every possible combination. These treatments remained for 48 hours in the dark and afterwards in growth room at the temperature of 27 ± 1oC with 16 hours lighting. After 40 days, seedlings were evaluated by the lengths of the aerial part and root system and percent of survival. The concentration of 0.1 mg/L of GA3 interacts negatively in culture medium containing up to 2.0 g/L of activated coal. The concentration of 0.01 mg/L of GA3 associated to activated coal concentration of 0.5 g/L to 2.0 g/L maximized the percentage of embryo survival. Embryos showed the highest length of root (4.5 cm) and shoot (2.1 cm) when cultivated in activated coal at 0.5 g/L and 2.0 g/L, respectively.